Relationship between gut microbiota and lymphocyte subsets in Chinese Han patients with spinal cord injury - Pang, Rizhao; Wang, Junyu; Xiong, Yisong; Liu, Jiancheng; Ma, Xin; Gou, Xiang; He, Xin; Cheng, Chao; Wang, Wenchun; Zheng, Jinqi; Sun, Mengyuan; Bai, Xingang; et al. (Frontiers in Microbiology, 2022)
This study is to investigate the changes of lymphocyte subsets and the gut microbiota in Chinese Han patients with spinal cord injury (SCI). We enrolled 23 patients with SCI and 21 healthy controls. Blood and fecal samples were collected. The proportion of lymphocyte subsets was detected by flow cytometry. 16S rDNA sequencing of the V4 region was used to analyze the gut microbiota. The changes of the gut microbiota were analyzed by bioinformatics. Correlation analysis between gut microbiota and lymphocyte subsets was performed. CD4+ cells, CD4+/CD8+ ratio and CD4+CD8+ cells in peripheral blood of SCI patients were significantly lower than those of the control group (P<0.05). There was no significant difference in B cells and CIK cells between the SCI group and the control group. The gut microbiota community diversity index of SCI patients was significantly higher than that of healthy controls. In SCI patients, the relative abundance of Lachnospiraceae (related to lymphocyte subset regulation), Ruminococcaceae (closely related to central nervous system diseases), and Escherichia-Shigella (closely related to intestinal infections) increased significantly, while the butyrate producing bacteria (Fusobacterium) that were beneficial to the gut were dramatically decreased. Correlation analysis showed that the five bacterial genera of SCI patients, including Lachnospiraceae UCG-008, Lachnoclostridium 12, Tyzzerella 3, Eubacterium eligens group, and Rumencocciucg-002, were correlated with T lymphocyte subsets and NK cells. In the SCI group, the flora Prevotella 9, Lachnospiraceae NC2004 group, Veillonella, and Sutterella were positively correlated with B cells. However, Fusobacterium and Akkermansia were negatively correlated with B cells. Moreover, Roseburia and Ruminococcaceae UCG-003 were positively correlated with CIK cells. Our results suggest that the gut microbiota of patients with SCI is associated with lymphocyte subsets. Therefore, it is possible to improve immune dysregulation in SCI patients by modulating gut microbiota, which may serve as a new therapeutic method for SCI.